Colors Sorting System (CSS) - Meera Adli Saymeh; Masa Jamal Al-Sayyed (My University, 2023)
Sorting Objects in a specific way whether it is by color or bar code or anything else is beneficial in many aspects, and makes it easier for the workers. The colors sorting system is mainly used now in agricultural grain and rice, as well as in the processing of food products, such as coffee, nuts, and oil crops. Colors Sorting system (CSS) senses when there is an object on the color sensor and depending on that color the arm will put the object in a cell in the column that is specified for that color. There are two ways to retrieve a specific object: Push buttons and Keypad, there are four push buttons for the four colors used each push button retrieves the object from the cells according to order and puts the object near where it was placed for the sensor, the Keypad is for all the eight cells used when clicking on a cell number the arm will take the object and place it in a container to take the container out at the end.